Clinical Post-Abortion Contraceptive Acceptance and Choice Among Women Receiving Abortion Care at Tertiary Center In Chitwan District, Nepal - Shrestha, Rubina; Shrestha, Buddhi Kumar; Shrestha, Subha; Acharya, Manish; Baniya, Puja (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To find out the acceptance of contraception after abortion and the factors affecting its use.Methods: A prospective cross sectional study was carried out from February 2020 to February 2021 on women seeking safe abortion care services in College of Medical Sciences Teaching Hospital, Chitwan, Nepal. A systematic sampling technique was used to reach the sample size.Results: Out of total 200 women who came for safe abortion 73% participant had induced abortion and 27% had spontaneous abortion. The main reason for induced abortion was completed family (43.3%).The acceptance rate of contraceptive was 78%. Most frequently used contraceptive was oral contraceptive pill (OCP) followed by depo- provera. The age of the patient, high parity, number of living children, reason for abortion and family planning counseling were independent factors that increase the acceptance of contraceptive post abortion. The education, occupation, past history of contraceptive use and abortion although did not affect the use of contraceptives.Conclusions: This study shows that if we give proper contraceptive counseling post-abortion, acceptance rate of contraceptives can be increased. Therefore, family planning services after abortion need to be strengthened.